Edukasi Mp ASI 4* Home Made Dengan Bahan Pangan Lokal - Widaryanti, Rahayu (Universitas Respati Yogyakarta, 2020)
The percentage of toddlers who are very short and short of age 0-59 months in Indonesia in 2018 is 11.5% and 19.3%. This condition increased from the previous year, namely the percentage of toddlers aged 0-59 months was very short at 9.8% and short toddlers at 19.8%. In the Special Region of Yogyakarta the incidence of stunting is also still quite high at 27.2%. In Sleman Regency the prevalence of nutritional status of toddlers was short and very short in 2017 an increase of 0.18% compared to 2016, from 11.81% to 11.99%. One of the factors causing Stunting in Sleman Regency is the lack of parental knowledge about giving the right complementary feeding, which causes toddlers to get less optimal nutrition. Identification of problems in depth such as difficulty in breastfeeding, reduced breastmilk syndrome, toddlers who are picky eater have not been done optimally and comprehensively. In addition, from the pre-test results conducted before educational activities, there were 56% of mothers under-five who did not understand the right complementary feeding for their children, most parents gave instant complementary feeding and bought complementary feedingin the market or baby porridge sales outlets. The activity was attended by 25 mothers who had children under the age of 24 months. To measure the success of this activity, pre-test and post-test were carried out. The result of devotion is that after participating in complementary feeding educational activities the level of knowledge of mothers about complementary feedinghas increased, before participating in the activity the number of mothers who have a high level of knowledge only 4% after participating in the activity increased to 44%. With increasing knowledge about complementary feedingit is expected that mothers can apply their knowledge in providing home made complementaryÂ feedingwith local materials that are in accordance with WHO and Unicef recommendations.Keywords: education, complementary feeding, home made